Neighborhood-level income and MRSA infection risk in the USA: systematic review and meta-analysis - Sarah Blackmon; Esther E. Avendano; Sweta Balaji; Samson Alemu Argaw; Rebecca A. Morin; Nanguneri Nirmala; Shira Doron; Maya L. Nadimpalli (BMC Public Health)
Abstract Background The impact of neighborhood-level income on community-associated methicillin-resistant S. aureus (CA-MRSA) risk remains poorly understood, despite established associations between MRSA risk and the social determinants of health. There are conflicting findings in the existing literature and no known systematic reviews based in the U.S. Our objective was to conduct a systematic review and meta-analysis of the association between neighborhood-level income and CA-MRSA in the U.S. Methods We searched MEDLINE (Ovid), MEDLINE Epub Ahead of Print, In-Process, In-Data-Review & Other Non-Indexed Citations, and Daily (Ovid), Global Health (Ovid), Embase (Elsevier), Cochrane Database of Systematic Reviews (Wiley), Cochrane Central Register of Controlled Trials (Wiley), and Web of Science Core Collection from 2017 to 10 January 2021. An updated search was completed in November 2023. Eligible studies reported stratified CA-MRSA case counts and/or effect measures by neighborhood income level, reported as a categorical or continuous variable. Relevant data were extracted using Covidence following the PRISMA guidelines. A random-effects model meta-analysis was used to estimate the pooled effect measure. Three study design-specific risk of bias assessments and a quality assessment were applied using the modified Newcastle-Ottawa Quality Assessment Scale and GRADE approach, respectively. Results Six publications met eligibility criteria. Five found that living in a low-income neighborhood was associated with increased CA-MRSA risk. Among the four studies eligible for the meta-analysis, the pooled odds ratio for CA-MRSA infection among low vs. high-income neighborhoods (reference group) was 1.28 (95% CI: 1.13, 1.46), with statistical heterogeneity (I2 73%). Limiting to low risk of bias studies (n = 3), there was no significant relationship between low income and CA-MRSA infection (OR: 1.13, 95% CI: 0.96, 1.33) with heterogeneity of 0%. Conclusions Evidence supports an association between lower neighborhood income and higher CA-MRSA infection risk, albeit with considerable heterogeneity. Future studies should consider evaluating neighborhood-level income as a continuous variable, and at the block-group level to avoid exposure misclassification. Furthermore, researchers should consider adjusting for covariates that could allow for a causal interpretation of the relationship between low neighborhood-level income and CA-MRSA risk.